Analisis Efisiensi Saluran Primer Di Daerah Irigasi Sei Paku - Ahmad Fauzi; Mudjiatko Mudjiatko; Sigit Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Irrigations networks in irrigations areas of Sei Paku have a very low efficiency value due to the exploitations of fish ponds and recreations ponds. Exploitations activities on the upstream is watering fish ponds and recreatiol ponds that’s effect is water loss, so make deffeclency water at downstream areas. Result water loss on the flow influence at primary flow. Efficiency analysis flow use to know efficiency primary flow. Topographic data, speed flow, and dimensions of channel are needed to analyze the value of primary flow efficiency existing in the field. Efficiency analysis is done by directly measurement in the area as much as 5 periods. Based on the analysis results that the biggest water loss at T45 – T61 segmen as much Qt = 0.0960021 m3/second and smallest water loss at T91- T101 segmen as much Qt = 0.0000007 m3/second. The efficiency of the existing pyrene channel in the field is 9.41%.Keywords : Irrigations Areas Sei Paku, waterloss, and efficienc.